Pengaruh Motivasi dan Tingkat Pendapatan Orangtua Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS di SMPN 2 Batang Anai Kecamatan Batang Anai Kabupaten Padang Pariaman - Nengsih, Elda; Suarto, Dedi; Prarikeslan, Widya (STKIP PGRI Sumbar, 2013)
This research used descriptive correlational research. The populations in this research were all parents in SMP N 2 Batang Anai at eighth grade students are 185 peoples. The sample of respondents was taken by purposive sampling technique by taking classes that have average values below the KKM and the average value over the KKM. The samples taken are two classes, VIII.2 and VIII.3 which has about 74 students. Based on the results of correlation and regression analysis, the obtained results as follows: first, there is a significant and positive relationship between the motivation of parents of student learning outcomes in social studies in SMPN 2 Batang Anai district of Padang Pariaman because thitung>ttabel; (4.686> 1.666), including moderate strength (r = 0.483) and the contribution which includes a small (23.4%), second, there is a significant and positive relationship between parental income on student learning outcomes in social studies in SMPN 2 Batang Anai District Padang Pariaman because t hitung >ttabel; (2.569> 1.666), the strength of the relationship is low (r = 0.290) and the contribution is very small (8.4%) and third there is a significant and positive effect the motivation of parents and parental income together toward student learning outcomes in social studies in SMPN 2 Batang Anai Sub District Padang Pariaman because fhitung>ftabel (12.249> 3.20), the strength of the relationshsip between two variables is to Y variables including moderate (r = 0.506) and the contributions made small (25.7%).